ASSESSMENT OF THE RESULTS OF NEWBORN SCREENING BY HEALTH BLOOD LETS AT NGHỆ AN OBSTETRICS AND PEDIATRICS HOSPITAL FROM JANUARY TO JUNE 2022 (Vietnam Journal of Community Medicine, 2022)
Background: Newborn Screening is a screening program that helps to detect common andtreatable or preventable congenital metabolic-endocrine and genetic disorders in newborn babies.Detected through a screening test kit for 5 diseases: G6PD deficiency, congenital hypothyroidism,congenital adrenal hyperplasia, Galactosemia, PhenylketonuriaObjectives: Determine the rate of newborns at high risk of 5 diseases and the relationship withepidemiological factors.Methods: Using cross-sectional descriptive method for newborns full 24-72 hours old born atNghe An Obstetrics and Pediatrics Hospital from January 2022 to June 2022.Results: Through surveying 3147 samples of heel in newborns, we found that the abnormal rateof newborn screening tests accounted for the following: G6PD deficiency accounted for 0,86%, ofwhich, male accounted for 70,37%, girls account for 29.63%. Congenital hypothyroidism is0.22%. Congenital adrenal hyperplasia is 0,13%. Phenylketonuria was 0,1% and none of thechildren were in the high-risk group for galactosemia.Conclusions: 5 newborn screening diseases, if detected early, can be prevented and treated sothat children can have a completely healthy life. Therefore, it is necessary to strengthen screeningcounseling to improve population quality and improve living standards.
Keywords: Newborn screening, heel prick test.